OPTIMALISASI PENGGUNAAN WEBSITE WWW.PERADAH.ORG SEBAGAI MEDIA PUBLIKASI DI DEWAN PIMPINAN NASIONAL PERHIMPUNAN PEMUDA HINDU INDONESIA - Sundari Janur Anggita, Indra Prameswara, Made Jaya Negara, Wayan Arif Sugiarta (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2020)
As long as it is been a lot of articles or information associated peradah indonesia www.peradah.org, published through his website lately a decline in both in the number of article being published and also read in every, information sharing so that it takes a special effort by the dpn peradah indonesia to the process of the management of information on a website. Based on the background, showed up some formula problems related to how Indonesia manages peradah on publication of information through websites www.peradah.org. General objectives of the study is aimed to know anything that got in the becomes strategy the form of a strengthening the existence of an organization that started as actions have been held by by perhimpunan pemuda hindu ( peradah ) indonesia and he damaged figure out how to peradah indonesia manage the broad range of areas of publications information and on the website www.peradah.org. Was used in the study a method of dekskriptif qualitative with the nature of research as well as desktiptif qualitative adopts a qualitative approach to to explain a strategy of the form of a strengthening of the jeddah based organization the existences of Indonesian hindu youth association through the publication of at the website www.peradah.org. A theory that used in this research is a theory corporate information about.The research was conducted in graha synergy peradah Indonesia. The process of collecting the data in this research through many different phases that is, observation, interviews and documentation. The result of research that www.peradah.org website not just as a source of information but is also capable of opening access to extensively in tissue to limited human resources and the operational cost of. So that openness and the needs of information have been accommodated through of websites which managed entirely by peradah Indonesia.